Prevalence of non-specific chronic low-back pain and risk factors among male soldiers in Saudi Arabia - Sidiq,Mohammad; Alenazi,Wadha; Kashoo,Faizan Z.; Qasim,Mohammad; Lopez,Marisia Paz; Ahmad,Mehrunnisha; Mani,Suresh; Shaphe,Mohammad Abu; Khodairi,Omaymah; Almutairi,Abdulqader; Mir,Shabir Ahmad (PeerJ, 2021)
Background Non-specific chronic low back pain (NSCLBP) is the most common musculoskeletal disorder affecting health and work among the military population. NSCLBP is a complex disorder with several risk factors contributing to its occurrence. Therefore, the objective of our study was to estimate the prevalence and contribution of risk factors towards NSCLBP among male soldiers in Saudi Arabia. Methods A cross-sectional study was conducted from March 2020 to January 2021 among the military personnel at Hafar Al-Batin military base, Saudi Arabia. The entire population (n = 62, 000) at the military base were invited to participate in the study. The participants were invited to participate in the study either through direct referral from in-patient and out-patient departments of the military hospital or by invitation through pamphlets, email, and advertisement across the offices and residential areas. Soldiers reporting lower back pain for at least 12 weeks were screened for inclusion criteria at the physical therapy department of the military hospital. Inclusion criteria included pain or discomfort originating from the lower back without any known spinal diseases. Participants with a systemic inflammatory disorder, trauma, neurological symptoms, and recent spinal surgery were excluded. All eligible participants were assessed for demographic variables and risk factors and complete the Rolland Morris Disability Questionnaire and WHO-Five Well-Being Index. Results This study identified a 46.3% prevalence of pain originating from the spine with a 2.7% prevalence of NSCLBP. Spearman’s rho correlation between the severity of disability due to NSCLBP was strongly associated with age (rs = 0.834, p < 0.01), quality of sleep (rs = 0.790, p < 0.01), body mass index (BMI) (rs = 0.617, p < 0.01), smoking (rs = 0.520, p < 0.01), co-morbidity (rs = 0.357, p < 0.01), but not with the level of physical activity (rs = 0.044, p = 0.07). Conclusion There was a high prevalence of pain originating from the spine among male Saudi soldiers with a relatively low prevalence of NSCLBP. However, the prevalence of disability due to NSCLBP was strongly associated with age, sleep quality, BMI, smoking habit, and co-morbidity.
Keywords: Backache; Prevalence; Soldiers; Military; Risk factors; Musculoskeletal disorders